Design, Synthesis, and Cholinesterase Inhibition Assay of Coumarin‐3‐carboxamide‐N‐morpholine Hybrids as New Anti‐Alzheimer Agents. Issue 7 (26th June 2019) - Tehrani, Maliheh Barazandeh; Rezaei, Zahra; Asadi, Mehdi; Behnammanesh, Hossein; Nadri, Hamid; Afsharirad, Fatemeh; Moradi, Alireza; Larijani, Bagher; Mohammadi‐Khanaposhtani, Maryam; Mahdavi, Mohammad
Abstract: A new series of coumarin‐3‐carboxamide‐ N ‐morpholine hybrids5a –5l was designed and synthesized as cholinesterases inhibitors. The synthetic approach for title compounds was started from the reaction between 2‐hydroxybenzaldehyde derivatives and Meldrum's acid to afford corresponding coumarin‐3‐carboxylic acids. Then, amidation of the latter compounds with 2‐morpholinoethylamine or N ‐(3‐aminopropyl)morpholine led to the formation of the compounds5a –5l . The in vitro inhibition screen against acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) revealed that most of the synthesized compounds had potent AChE inhibitory while their BuChE inhibitions are moderate to weak. Among them, propylmorpholine derivative5g ( N ‐[3‐(morpholin‐4‐yl)propyl]‐2‐oxo‐2 H ‐chromene‐3‐carboxamide) bearing an unsubstituted coumarin moiety and ethylmorpholine derivative5d (6‐bromo‐ N ‐[2‐(morpholin‐4‐yl)ethyl]‐2‐oxo‐2 H ‐chromene‐3‐carboxamide) bearing a 6‐bromocoumarin moiety showed the most activity against AChE and BuChE, respectively. The inhibitory activity of compound5g against AChE was 1.78 times more than that of rivastigmine and anti‐BuChE activity of compound5d is approximately same as rivastigmine. Kinetic and docking studies confirmed the dual binding site ability of compound5g to inhibit AChE. Abstract :